Division of Labour, Work–Life Conflict and Family Policy: Conclusions and Reflections - Ochsner, Michael (2020)
This thematic issue aims to shed light on different facets of the relationship between division of labour within families and couples, work–life conflict and family policy. In this afterword, we provide a summary of the contributions by emphasizing three main aspects in need of further scrutiny: the conceptualisation of labour division within families and couples, the multilevel structure of relationships and the interactions of gender(ed) values at different levels of exploration.